A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMPN 13 PEKANBARU IN COMPREHENDING DESCRIPTIVE TEXTS - Witri Rahmadhaningsi Tiyas; Fadly Azhar; Mahdum Mahdum (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was designed to describe the student’s ability in comprehending descriptive texts and aimed to find out the students ability in comprehending descriptive texts. This research was conducted at SMPN 13 Pekanbaru that collected May to June 2017. The try out class was VIII-4 (30 students) and the sample was VIII-1 (30 students) chosen by cluster random sampling. The result showed that the ability of the second year students of SMPN 13 Pekanbaru in comprehending descriptive texts for each component is in good level which the mean score was 66.5, however, the students have not passed the minimum score of the school which is 80. finding factual information the mean score was 74, finding meaning of vocabullary was 59.3, finding references the mean score was 66.6, finding main idea the mean score was 70, finding inference was 60, and finding social function was 69.3. Therefore, this research suggested the English teachers to give extra time in giving explanation about reading texts and the students should learn the components in descriptive texts that will help them in comprehend other reading texts.Key Words: Student’s Ability, Comprehending Descriptive Texts.